Perspectives in Molecular Imaging Using Staging Biomarkers and Immunotherapies in Alzheimer’s Disease - Benoît Leclerc; Abedelnasser Abulrob (The Scientific World Journal)
Sporadic Alzheimer’s disease (AD) is an emerging chronic illness characterized by a progressive pleiotropic pathophysiological mode of actions triggered during the senescence process and affecting the elderly worldwide. The complex molecular mechanisms of AD not only are supported by cholinergic, beta-amyloid, and tau theories but also have a genetic basis that accounts for the difference in symptomatology processes activation among human population which will evolve into divergent neuropathological features underlying cognitive and behaviour alterations. Distinct immune system tolerance could also influence divergent responses among AD patients treated by immunotherapy. The complexity in nature increases when taken together the genetic/immune tolerance with the patient’s brain reserve and with neuropathological evolution from early till advance AD clinical stages. The most promising diagnostic strategies in today’s world would consist in performing high diagnostic accuracy of combined modality imaging technologies using beta-amyloid 42 peptide-cerebrospinal fluid (CSF) positron emission tomography (PET), Pittsburgh compound B-PET, fluorodeoxyglucose-PET, total and phosphorylated tau-CSF, and volumetric magnetic resonance imaging hippocampus biomarkers for criteria evaluation and validation. Early diagnosis is the challenge task that needs to look first at plausible mechanisms of actions behind therapies, and combining them would allow for the development of efficient AD treatment in a near future.